Stock Market Manipulation: A Literature Review - Maxim, Maruf Rahman (Asian Accounting and Auditing Advancement, 2016)
This paper classifies the major types of stock market manipulation that have been observed over the past 30 years. The key objective of this paper is to summarize the findings of some of the leading research works done on stock market manipulation. This paper also talks about some of the major incidences of stock market manipulation that took place in various developed financial markets. Research on stock market manipulation is scarce, and this paper tries to give a holistic view of it to better understand it. Market manipulation is a dynamic problem. It’s been changing with time, with the advancement of technology, and with the evolution of financial markets. This paper exhibits this characteristic of stock market manipulation and explains how it has been changing over time. JEL Classification Code: G14